Perfil del microempresario y formalización en la ciudad de Requena 2024 - Paredes Pizarro, Norma Esther (2025)
This study aimed to analyze the relationship between microentrepreneur characteristics and the degree of formalization in the city of Requena during the period 2024. To achieve this objective, a sample of 65 individuals belonging to this sector was selected, who were then administered a questionnaire specifically designed for data collection. The results obtained showed that 29% of respondents considered the microentrepreneur profile to be average. This assessment was mainly due to the fact that, according to participants, only in certain specific contexts do microentrepreneurs demonstrate sufficient creativity and innovation to significantly improve their businesses. Furthermore, formalization also received a predominantly average rating, being selected by 28% of respondents. This assessment is due to the fact that some companies, in particular cases, do not adequately select the personnel they require to properly perform their commercial functions. Finally, when examining the relationship between the microentrepreneur profile and the level of formalization, a positive coefficient of 0.887 was found, indicating a fairly strong favorable correlation between the two variables. This result was statistically validated using a two-tailed significance level of 0.000, thus confirming the robustness of the findings obtained in the study conducted in Requena.